Atrial fibrillation and stroke risk of patients with hypertrophic cardiomyopathy in denmark from 2005-2018: a nationwide cohort study. (19th May 2022) - Zoerner, CR; Pallisgaard, J; Schjerning, AM; Toennesen, J; Jensen, MK; Gislason, G; Hansen, ML
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Internal funding: Herlev-Gentofte Cardiovascular Research Department. Background: Hypertrophic cardiomyopathy (HCM) can be associated with serious complications such as heart failure, atrial fibrillation (AF) and sudden cardiac death. The treatment of AF in HCM patients can be challenging since AF often aggravates symptoms. Previous studies have suggested that HCM patients with AF have an elevated risk of thromboembolism and stroke compared to AF patients without HCM regardless of their CHA2DS2VASc score. Purpose: To determine the risk of AF and stroke in HCM patients. Methods: Through the Danish National Registers all patients aged 16 or older diagnosed with HCM between the 1st of January 2005, and the 31st of December 2018 were included in the analysis. The association between HCM, AF, and stroke was investigated using multivariable Cox proportional-hazard analysis adjusted for gender, age, atrial fibrillation, ischemic heart disease, chronic obstructive pulmonary disease, chronic kidney disease and hypertension. Cumulative incidence of AF and stroke was calculated using the Aalen-Johansen estimator, taking death as a competing risk into account. Results: A total of 3856 patients were included, 2060 (53, 4%) were male and median age of 67, 8 (IQR 56 and 77, 8) years. During the study period, 384 (10%) patients were diagnosed with AF. The risk of AF was significantly lower in males (HR 0, 72 (0, 59–0, 90), p-value = 0.003) and for patients below 60 years (HR 0, 18 (0, 12–0, 27), p-value = <0.001). (Figure 1) 157 (4, 1%) of the HCM patients developed stroke. The risk of developing stroke was significantly decreased for patients aged under 60 (HR 0, 32 (0, 2–0, 52), p-value = <0.001). There was no increased risk of stroke comparing genders. Stroke risk was further analyzed in patients with known AF at time of inclusion, 656 (17%) in total. Compared to patients without AF and adjusted for age, gender and co-morbidities, there was no significant difference in stroke risk between these groups (HR 1.2 (0, 81-1, 76), p-value = 0.36). (Figure 2) Conclusion: AF and stroke are common complications in HCM. Women are more susceptible to developing AF than men, and age over 60 at the time of diagnosis was associated with significantly higher risk of AF and stroke. HCM patients with previously known AF did not have a significantly elevated risk of stroke. More research will be needed to further explore these connections.